Submarine Infrastructures and the International Legal Framework - Halog, Jason; Margat, Paul; Stadermann, Michael (Transactions on Maritime Science, 2024)
The purpose of this paper is to identify weaknesses in the international framework for the protection of submarine cables beyond the sovereign waters of coastal States. To illustrate this, the paper uses a hypothetical case study of what a possible attack on a submarine cable may look like. First, it provides an overview over the applicable framework, with a particular focus on international peacekeeping law (ius contra bellum), the law of the sea, protection against piracy, and criminal prosecution under national criminal law. Various international conventions play a key role in relation to submarine cables. Particularly relevant are the Convention on Submarine Telegraph Cables of 1884, the United Nations Convention on the Law of the Sea of 1982, as well as the peacekeeping regulations of the United Nations Charter of 1949. After outlining the legal framework using the classical methods of treaty interpretation, as well as taking the scholarly literature on this subject into account, the example is subsumed under the various means of protection under international law. The peacekeeping law of the United Nations turns out to be ineffective because, on the one hand, an attack as described in the reference scenario does not necessarily constitute an armed attack in the sense of the UN Charter and therefore cannot be met with military countermeasures. On the other hand, an authorisation by the Security Council cannot be given quickly enough to counter the attack militarily. In addition to that, measures taken in the framework of the Law of the Sea Convention are ineffective due to the exclusive flag State jurisdiction which precludes other States from acting in this matter. An exception to this principle, namely universal jurisdiction to combat piracy, is unlikely to be applied in the context of an attack against a submarine cable. Finally, as result of the exclusive jurisdiction of the flag State and the poor implementation of the international obligations under the Law of the Sea Convention, national criminal law is also inadequate as a repressive means of protection.